RELATIONSHIP BETWEEN PERSONALITY TRAITS, GOD’S IMAGE, RELIGIOSITY AND RELIGIOUS COPING IN LATVIAN ROMAN CATHOLIC ADULTS’ SAMPLE - Trups-Kalne, Ingrīda; Perepjolkina, Viktorija; Lietaviete, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The present study aims to examine the relationship between personality traits, God image and religious coping (RC) among Roman Catholics in Latvia. There were 336 respondents, aged 18 ‒ 86. We applied the Brief (RCOPE), God Image Scale (GIS), Latvian Personality Inventory (LPAv-3), The Centrality of Religiosity Scale CRS-5, including demographic data. The results showed positive correlation between Neuroticism and negative RC, but negative correlation with positive RC. Such personality traits as Openness, Conscientiousness and Agreeableness correlated positively with positive RC. Also Honesty-Humility and God Image correlated positively with positive RC and negatively – with negative RC. The study showed positive correlations between some dimensions of religiosity (and positive RC. Religious ideology and religious experience correlated negatively with negative RC. The study revealed that on the scale level the most relevant predictors of positive religious coping are scales such as religiosity and image of God, and personal traits such as agreeableness and openness. Likewise it was identified that on the scale level the most relevant predictors of negative religious coping are scales such as image of God, neuroticism and religiousness. These findings suggest tenets for psychological and pastoral interventions to decrease the impact of negative RC.